Accumulation and developmental toxicity of hexabromocyclododecanes (HBCDs) on the marine copepod Tigriopus japonicus. (January 2017) - Shi, Dalin; Lv, Dongmei; Liu, Wanxin; Shen, Rong; Li, Dongmei; Hong, Haizheng
Abstract: The brominated flame retardants hexabromocyclododecanes (HBCDs) are ubiquitous environmental contaminants, widely distributed in aquatic systems including the marine environment and marine organisms. HBCDs are toxic to the development of both freshwater and marine fish. However, the impacts of HBCDs on marine invertebrates are not well known. In this study, the marine copepod, Tigriopus japonicus, was used to assess the bioaccumulation and developmental toxicity of technical HBCD (tHBCD) through water-borne exposure. The uptake rate constant of tHBCD by T . japonicus was high, which resulted in high bioaccumulation potential. The bioconcentration factors of tHBCD were 8.73 × 10 4 and 6.34 × 10 4 L kg −1 in T . japonicus, calculated using the kinetic and steady-state methods, respectively. Exposure of T . japonicus nauplii to tHBCD caused significant growth delay. The lowest-observable-effect-concentrations of tHBCD induced developmental delay were 30 and 8 μg L −1 for the F0 and F1 generations, respectively, which suggested that the F1 generation was more sensitive to tHBCD than the F0 generation and warranted multiple-generation toxicity tests for future studies. Furthermore, exposure of the adult copepods to tHBCD induced the transcription of oxidative stress response genes and apoptotic genes, e.g., SOD, CAT, GST, OGG1, P53 and Caspase-3. It was therefore speculated that tHBCD exposure induced the generation of reactive oxygen species in T . japonicus, which activated the oxidative stress defense genes and meanwhile resulted in oxidative DNA damage. The damaged DNA activated the transcription of p53 and triggered the caspase-mediated apoptosis pathway, which may be the reason for the tHBCD induced developmental delay in T . japonicus nauplii. Highlights: HBCD had high bioaccumulation potential in T . japonicus . HBCD caused developmental delay in T . japonicus . The F1 generation of T . japonicus was more sensitive to HBCD than the F0 generation. HBCD induced oxidative stress in T . japonicus .